Diversity of Interferon Antagonist Activities Mediated by NSP1 Proteins of Different Rotavirus Strains - Arnold, Michelle M. (American Society for Microbiology (ASM), 2011)
Studies involving limited numbers of rotavirus (RV) strains have shown that the viral gene 5 product, NSP1, can antagonize beta interferon (IFN-β) expression by inducing the degradation of IFN-regulatory factors (IRFs) (IRF3, IRF5, and IRF7) or a component of the E3 ubiquitin ligase complex responsible for activating NF-κB (β-transducin repeat-containing protein [β-TrCP]). To gain a broader perspective of NSP1 activities, we examined various RV strains for the ability to inhibit IFN-β expression in human cells. We found that all strains encoding wild-type NSP1 impeded IFN-β expression but not always through IRF3 degradation. To identify other degradation targets involved in suppressing IFN-β expression, we used transient expression vectors to test the abilities of a diverse collection of NSP1 proteins to target IRF3, IRF5, IRF7, and β-TrCP for degradation. The results indicated that human RVs rely predominantly on the NSP1-induced degradation of IRF5 and IRF7 to suppress IFN signaling, whereas NSP1 proteins of animal RVs tended to target IRF3, IRF5, and IRF7, allowing the animal viruses a broader attack on the IFN-β signaling pathway. The results also suggested that the NSP1-induced degradation of β-TrCP is an uncommon mechanism of subverting IFN-β signaling but is one that can be shared with NSP1 proteins that induce IRF degradation. Our analysis reveals that the activities of NSP1 proteins are diverse, with no obvious correlations between degradations of pairs of target proteins. Thus, RVs have evolved functionally distinct approaches for subverting the host antiviral response, a property consistent with the immense sequence variation noted for NSP1 proteins.